CONTRIBUTION OF THE PERUVIAN SOCIETY OF OBSTETRICS AND GYNECOLOGY - Guevara Ríos, Enrique (2025)
The Peruvian Society of Obstetrics and Gynecology (SPOG) celebrates 78 years since its foundation on June 30, 1947, an event that marked a milestone in the development of the specialty in Peru. Under the presidency of Dr. Constantino José Carvallo Alzamora, the institution was consolidated as an academic and scientific reference. Among its achievements are the creation in 1955 of the Peruvian Journal of Gynecology and Obstetrics, the organization of biennial congresses since 1959, and the official recognition in 1998 of June 30 as the Day of Peruvian Gynecology and Obstetrics. Throughout its history, 58 presidents and their boards of directors have promoted research, teaching, and professional excellence, making significant contributions to maternal and reproductive health in the country.